KETELADANAN DAN PROFESIONALISME GURU SERTA KAITANNYA DENGAN KEMANDIRIAN BELAJAR DAN AKHLAK SISWA - Didit Darmawan; Rizky Fitra Auliya (Jurnal Bilqolam Pendidikan Islam, 2026)
This literature study aims to analyze the contribution of teacher example and professionalism to the formation of student learning independence and morals. Using a qualitative library research approach, this study synthesizes concepts from various relevant theoretical sources. The findings indicate that teacher example contributes through identification and value internalization mechanisms, where students imitate the attitudes and behavior of teachers who are consistent between words and actions. Honest, patient, fair, responsible, and humble teachers become concrete models that shape student morals while inspiring learning independence. Teacher professionalism contributes through empowering learning planning, varied method selection, conducive classroom management, constructive feedback, and creating a learning community that respects moral values. Professional teachers design learning experiences that train student self-regulation, metacognition, and responsibility, while systematically integrating values. Both teacher qualities are complementary and mutually reinforcing. Example without professionalism produces sporadic impacts, while professionalism without example loses the spirit of education. The synergy between the two produces integrated education that shapes students who are independent in learning and noble in morals.